Indonesia's role in the internationalization of halal tourism through national policy and multilateral diplomacy - Wibiksono, Almirah Nahda Ayu; Farasyah, Nazwa (Priviet Social Sciences Journal, 2026)
This study is motivated by the growing global acknowledgment of halal tourism as a pivotal sector within the halal industry and a significant engine for the Islamic economy. This study seeks to analyze Indonesia's role in internationalizing halal tourism by examining the synergy between its national policy development and its active participation in diplomatic forums, both of which serve as instruments for expanding its global influence. Methodologically, this qualitative study employs a systematic literature review, supplemented by content analysis of government regulations, policy documents, reports from international organizations, and relevant scientific articles on global halal tourism governance. The findings indicate that Indonesia strategically positions halal tourism as a domestic economic priority and a form of soft power. This can be achieved by strengthening halal certification, providing institutional support, engaging in nation branding, and promoting the harmonization of standards through multilateral cooperation. By leveraging multilateral diplomacy, Indonesia actively participates in shaping international norms, standardization, and networks to advance a more inclusive and globally recognized Halal tourism ecosystem. This strategy is not solely economically driven but also serves to enhance Indonesia's epistemic authority and diplomatic stature internationally. In conclusion, this study enriches the discourse on halal governance, international political economy, and tourism diplomacy, while also offering practical insights into Indonesia's potential to develop a competitive, sustainable, and influential halal tourism model through the effective synergy of national policies and multilateral engagement.